Debut. A course of russian for international students - Snegurova, T.; Romanov, Yu.; Paramonova, V. (National Technical University "Kharkiv Polytechnic Institute", 2019)
The text-book includes a range of material to give students the essential skills and knowledge they need for Russian reading, speaking, and writing from level A2 (“Russian for beginners”) up to B1 (“Debut 1”) and B2 (“Debut 2”) according to Council of Europe language descriptor. This course is intended for a very wide audience of Russian language learners, pursuing various goals (living and studying in those countries where Russian is spoken; short-term Russian courses; traineeship; language credits, etc.).

Учебник содержит материалы, имеющие целью формирование у студентов знаний и навыков российского чтения, говорения и письма от уровня А2 ("Russian for beginners") до уровня В1 ("Debut 1") и уровня В2 ("Debut 2") по языковому дескриптору Совета Европы. Учебник предназначен для широкого круга студентов, которые изучают русский язык для разных целей (проживание и обучение в странах, где говорят на русском; краткосрочные курсы русского языка, стажировка, получение академических кредитов по иностранному языку и т. д.).
Дебют. Курс русского языка для иностранных студентов
Keywords: учебник; язык русский; язык иностранный; студенты-иностранцы